2011
DOI: 10.1039/c1cc15220c
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-directed assembly and manipulation of organic nanomaterials

Abstract: Enzymes are the prime protagonists in the chemistry of living organisms. As such, chemists and biologists have long been fascinated by the array of highly selective transformations possible under biological conditions that are facilitated by enzymecatalyzed reactions. Moreover, enzymes are involved in replicating, repairing and transmitting information in a highly selective and organized fashion through detection and signal amplification cascades. Indeed, because of their selectivity and potential for use outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 83 publications
0
58
0
Order By: Relevance
“…1 Numerous ERMs have been developed based on hydrogel or micelle structures, which can be switched between assembled and disassembled forms using enzymes under mild conditions. 1,2 Although many different enzymes and substrates have been used in ERMs, most of these rely on bond formation or cleavage reactions that primarily employ proteases, nucleases, or kinases/phosphatases. Many ERMs also utilize specific peptide or oligonucleotide sequences as enzyme substrates, 1,2 which in turn increases the cost and complexity of ERM preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Numerous ERMs have been developed based on hydrogel or micelle structures, which can be switched between assembled and disassembled forms using enzymes under mild conditions. 1,2 Although many different enzymes and substrates have been used in ERMs, most of these rely on bond formation or cleavage reactions that primarily employ proteases, nucleases, or kinases/phosphatases. Many ERMs also utilize specific peptide or oligonucleotide sequences as enzyme substrates, 1,2 which in turn increases the cost and complexity of ERM preparation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although many different enzymes and substrates have been used in ERMs, most of these rely on bond formation or cleavage reactions that primarily employ proteases, nucleases, or kinases/phosphatases. Many ERMs also utilize specific peptide or oligonucleotide sequences as enzyme substrates, 1,2 which in turn increases the cost and complexity of ERM preparation. To enable widespread use of ERMs in various applications, such as diagnostics, sensors, drug delivery, adaptive surfaces, and regenerative medicine, it would be advantageous to be able to create ERMs that respond to different classes of enzymatic reactions, and that can be prepared using atom economical, scalable methods.…”
Section: Introductionmentioning
confidence: 99%
“…These concepts illustrate how the changes in the tumor microenvironment can be exploited clinically to detect small tumors that are otherwise difficult to localize. Other methods using labeled nanoparticles which can unravel to release their cargos in protease-rich tumor stroma [74] and/ or antibodies to preferentially concentrate in areas where the tumor cells juxtapose to stromal components [43] are under active exploration in some laboratories.…”
Section: Diagnostic Prognostic and Therapeutic Implications Of Undermentioning
confidence: 99%
“…As one of the non-covalent interactions, π-π stacking is vital to accelerate the alliance of supramolecular compounds to provide self-assembled structures with high stability [24]. Up to now, a lot of research for enzyme-responsive systems has been reported [25][26][27][28][29]. For instance, Zhang and coworkers have constructed several polymers by the electrostatic interaction between components responsive to phosphatase or acetylcholine [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%